The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/jhep02(2018)160
|View full text |Cite
|
Sign up to set email alerts
|

The clockwork supergravity

Abstract: We show that the minimal D = 5, N = 2 gauged supergravity set-up may encode naturally the recently proposed clockwork mechanism. The minimal embedding requires one vector multiplet in addition to the supergravity multiplet and the clockwork scalar is identified with the scalar in the vector multiplet. The scalar has a two-parameter potential and it can accommodate the clockwork, the Randall-Sundrum and a no-scale model with a flat potential, depending on the values of the parameters. The continuous clockwork b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 59 publications
(129 reference statements)
1
19
0
Order By: Relevance
“…The requirement is actually a little stronger than requiring solely supersymmetry, since the vacuum expectation value of the superpotential must also vanish to avoid supersymmetric AdS solutions. It has recently been shown that the CW/LD background is indeed consistent with a bulk supersymmetry [31,32]. Supersymmetry must be broken on the SM brane, however locality still protects against the generation of supersymmetry breaking in the bulk action (see e.g.…”
Section: Impact Of Cosmological Constant Termsmentioning
confidence: 99%
See 2 more Smart Citations
“…The requirement is actually a little stronger than requiring solely supersymmetry, since the vacuum expectation value of the superpotential must also vanish to avoid supersymmetric AdS solutions. It has recently been shown that the CW/LD background is indeed consistent with a bulk supersymmetry [31,32]. Supersymmetry must be broken on the SM brane, however locality still protects against the generation of supersymmetry breaking in the bulk action (see e.g.…”
Section: Impact Of Cosmological Constant Termsmentioning
confidence: 99%
“…[26] motivated by the seven-dimensional gravitational dual [27,28] of Little String Theory [29,30], which is a six-dimensional strongly-coupled non-local theory that arises on a stack of NS5 branes. Additionally, several recent studies have examined in more detail how the linear dilaton setup can be embedded in supergravity [31,32]. The clockwork interpretation of the linear dilaton theory has helped in elucidating its relation with Large Extra Dimension (LED) [33][34][35] and Randall-Sundrum (RS) [36] theories, thus providing a coherent map of approaches to the hierarchy problem in extra dimensions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28]. Motivated by the UV origin of the linear dilaton model as a dual description of the little string theory [28] (see also [36,37]), we consider the following 5D model with a universal dilaton coupling, which might be interpreted as the 5D action in the string frame:…”
Section: Jhep07(2018)113mentioning
confidence: 99%
“…In section 6 we shall discuss the clockwork mechanism from the 5D perspective and make connection to previous work that realises the linear dilaton model (LD) within 5Dsupergravity [56,57]. The other known bottom-up constructions (among them RS) can be embedded in this scheme.…”
Section: Introductionmentioning
confidence: 97%